Functionally ampicillin-stressed proteomics reveals that AdhE regulates alcohol metabolism for antibiotic resistance in Escherichia coli. (May 2021) - Li, Lu; Yang, Manjun; Zhu, Wei-cong; Liu, Xian-jie; Peng, Xuan-xian; Li, Hui
Graphical abstract: Highlights: Global protein profiling is characterized in ampicillin-resistant E. coli . Decreased central carbon metabolism and fatty acid biosynthesis deserves priority. Altered abundances of AdhE and FabG are identified as ampicillin-binding proteins. AdhE and FabG are the proteins targeted by the initiator antibiotics. Abstract: Antibiotic resistance is growing as a public health concern worldwide. Understanding of antibiotic-resistant mechanisms is especially necessary for control of the antibiotic resistance. The present study determined a proteome of Escherichia coli in response to ampicillin. The proteome consisted of 16-differential abundance of proteins, belonging to 8 pathways and constructing a protein-protein network. iPath analysis showed the reduced central carbon metabolism, oxidative energy production pathways, and fatty acid biosynthesis as the responsible processes. These data are supported by the decreased enzyme activity of the pyruvate cycle, NADH, membrane potential, and ATP. Moreover, the present study identified AdhE and FabG as ampicillin-binding proteins from the 16-differential abundance of proteins. Further study was focused on the mechanism of adhE in the resistance. Ampicillin-stressed E. coli exhibited higher adhE expression with lower intracellular alcohol. However, loss of adhE lowered bacteria viability which was associated with high intracellular alcohol than ampicillin-stressed E. coli. Thus, AdhE plays a role in the resistance through regulation of intracellular alcohol. These findings are helpful in further understanding ampicillin resistance mechanisms.